The ruins of the castle in Koło in the light of the latest architectural and archaeological research, and their conservation issues - Piaskowska, Beata; Prarat, Maciej; Różański, Artur; Olszacki, Tomasz; Schaaf, Ulrich (Ruiny zamku w Kole w świetle najnowszych badań architektonicznych i archeologicznych oraz związana z nimi problematyka konserwatorska, 2022)
The ruins of the castle in Koło are one of the better-preserved examples of a stronghold from the times of Kazimierz Wielki in the lowlands. The building has been in a state of ruin since the 17th century. A prominent corner tower with a fragment of three curtains has survived to this day. The purpose of this text is to discuss the results of architectural and archaeological research carried out in the years 2019–2020 and the project of the castle’s partial protection. The analysis of the aforementioned research made it possible to state that the construction of the stronghold began with the residential tower in the northern part. Subsequently, a tower was built in the south-west corner. In the next few stages, curtain walls were erected, closing the courtyard. In the southern part there was a gatehouse. A different construction technique enables us to conclude that there were several workshops working on it, which used single-rack and overhang scaffolding. The condition of the ruins was so bad that it was necessary to arrange a project to protect parts of one of the walls, which was completed in 2020.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 47-58
Keywords: architektura; Middle Ages; castle; architectural research; archeological research; Koło; średniowiecze; zamek; badania architektoniczne; badania archeologiczne